Teachers' perceptions of the school functioning of Chinese preschool children with callous-unemotional traits and disruptive behaviors. (March 2023) - Cao, Xinyi; Somerville, M.P.; Allen, J.L.
Abstract: This qualitative study investigated teachers' views on differences in children with disruptive behavior and high versus low levels of callous-unemotional (CU) traits in response to classroom management strategies, instructional methods, and teacher-child and teacher-caregiver relationship quality. Twenty teachers from three Chinese preschools were interviewed about 40 children with disruptive behavior (aged 4–6 years). Teachers perceived children with CU traits to have more severe disruptive behavior, poorer quality teacher-child and teacher-caregiver relationships and to be less responsive to discipline. The implications of findings for school-based intervention promoting engagement and prosocial behavior for children with CU traits are discussed.